A data envelopment analysis approach for measuring the efficiency in continuous manufacturing lines: a case study. (1st January 2014) - Pourjavad, Ehsan; Shirouyehzad, Hadi
In the competitive contemporary world, every company tries to gain competitive edge. In order to gain which, managers need to consider and analyse the performance of their organisations and decide to improve it. There are various approaches to evaluate the performance, in which the criterion of efficiency of understudy units is being placed in efficiency frontier: Data envelopment analysis is one of these approaches that are designed in two radial and non-radial categories. In this paper, the method applied is proposed to compare and analyse similar units of industry on the basis of industry criteria using data envelopment analysis. Industry criteria are considered as inputs and outputs to resolve this problem with DEA. This methodology specifies the strengths and weaknesses of each industry units from industry criteria viewpoints. For a better description, 12 of parallel manufacturing lines from Chadormalu mining-industry company were analysed on the basis of maintenance, product and quality criteria.